Considerations on digital manufacturing processes - Menegasso, Guilherme; Prado, Gilberto (DAT Journal, 2024)
In this article we will present some considerations about digital manufacturing, specifically the 3D printing process and how it relates to the laser cutting process in the context of prototyping. These two processes allow parts and models to be made from comparatively cheap raw materials within product design prototyping. We see these two technologies present in laboratories at design, architecture and engineering universities, making it possible for students to come into contact with this technology very early on in their undergraduate studies. The so-called makerspaces and Fab Labs allow these technologies to be used, making them favorable learning environments. Knowing how to differentiate between the advantages of each process and how to use the most appropriate process to manufacture a piece has become essential in training new designers. We will discuss the differences, advantages and applications of each process in order to engage with the undergraduate design environment to better understand the application and use of these technologies.